The mediating role of affective commitment in the relationship between the strategic planning process and the organizational effectiveness: case study of the Jordanian ministry of interior - Obeidat, Shuroog Hassan Ali (2023)
Drawing upon the Resource-Based View, Harvard Policy Model, and the Synoptic planning theory, the primary goal of this study is to examine the mediating role of affective commitment in the relationships between strategic planning practices, (scanning intensity, planning flexibility, locus of planning, and planning horizon) and organizational effectiveness in Jordanian Ministry of Interior. 361 questionnaires were distributed to the respondents, of which, 243 responses were returned and used for the final analysis. The Partial Least Squares Structural Equation Modelling technique was used to evaluate the hypotheses. The finding shows that the direct link between the three dimensions of strategic planning (scanning intensity, planning flexibility, locus of planning) and organizational effectiveness, were significant and hence supported. It also revealed that the four hypotheses suggested for the direct association between strategic planning practices and affective commitment were all supported. The results further suggested that there is a direct link between affective commitment and organizational effectiveness. Furthermore, the results offered empirical evidence that affective commitment mediated the link between strategic planning (scanning intensity, planning flexibility, locus of planning, and planning horizon) and organizational effectiveness. Based on these results, the study recommends enhancing strategic planning practices and fostering affective commitment to improve organizational effectiveness. It suggests policy revisions, focused training, and the development of engagement programs as practical measures. The study’s theoretical contribution lies in its empirical validation of the mediating role of affective commitment within strategic planning and its practical implications for public sector strategic management.